STRUKTUR DAN FUNGSI TARI KEJEI DALAM UPACARA PERKAWINAN DI KELURAHAN TALANG ULU KABUPATEN REJANG LEBONG - Putri Sari Rezaki; Nerosti (Universitas Negeri Padang, 2026)
This study aims to describe and analyze the Structure and Function of the Kejei Dance in Wedding Ceremonies in Talang Ulu Village, Rejang Lebong Regency. This type of research is qualitative research with a descriptive analytical method. Data was collected through direct observation of the Kejei Dance performance in wedding ceremonies, structured and unstructured interviews with relevant informants, as well as documentation studies. The main research instrument is the researcher themselves, assisted by supporting tools such as cameras and writing instruments. This study aims to describe and analyze the structure and function of the Kejei Dance in wedding ceremonies in Talang Ulu Village, Rejang Lebong Regency. The focus of this study is to examine the relationship between movement structure and its function in wedding ceremonies. The research results indicate that the structure of the Kejei Dance performance consists of several important elements, namely the ceremonial actors, the structure of movement presentation, floor patterns, costumes, makeup, props (penei table), and accompanying music. The sequence of presentation begins with a welcoming dance performed by 5 female dancers, followed by Rejang-style silat by 2 male dancers accompanied by 2 guards behind the dancers, serving to welcome the arrival of the bride and groom and as a customary form of reception for the bride and groom entering the ceremonial arena. Next, the event continues with duduk nyambei, which functions as a joint deliberation and reflects the social values of the Rejang community, such as harmony and togetherness, before entering the core ritual of the Kejei Dance, where the bride and groom join the line of dancers so that the total number of dancers becomes odd. The movements of the Kejei Dance include the sambah menari movement, the bederap salah pinggang movement, the metik jari movement, the patah dayung movement, the sambah penyudo movement, and the mendayung movement.